ARID3A plays a key regulatory role in palmitic acid‐stimulated milk fat synthesis in mouse mammary epithelial cells. (14th February 2023) - Guo, Xudong; Qi, Hao; Lin, Gang; Yu, Jiaxiao; Zhang, Minghui; Gao, Xuejun
Abstract: Palmitic acid (PA) can stimulate milk fat synthesis in mammary gland, but the specific mechanism is still unclear. In our research, we aim to explore the role and corresponding mechanism of AT‐rich interaction domain 3A (ARID3A) in milk fat synthesis stimulated by PA. We found that ARID3A protein level in mouse mammary gland tissues during lactation was much higher than that during puberty and involution. ARID3A knockdown and gene activation showed that ARID3A stimulated the synthesis of triglycerides and cholesterol in HC11 cells, secretion of free fatty acids from cells and lipid droplet formation in cells. ARID3A also promoted the expression and maturation of SREBP1 in HC11 cells. PA stimulated ARID3A protein expression and SREBP1 expression and maturation in a dose‐dependent manner, and the PI3K specific inhibitor LY294002 blocked the stimulation of PA on ARID3A expression. ARID3A knockdown blocked the stimulation of PA on SREBP1 protein expression and maturation. We further showed that ARID3A was localized in the nucleus and PA stimulated this localization, and ARID3A knockdown blocked the stimulation of PA on the mRNA expression of SREBP1 . To sum up, our data reveal that ARID3A is a key mediator for PA to promote SREBP1 mRNA expression and stimulate milk fat synthesis in mammary epithelial cells.